Evaluation of multimodal transportation integration facilities at Serang station - Anggun Nur Oktaviani; Muhammad Oka Mahendra (Journal of Infrastructure Planning and Engineering, 2025)
This study aims to evaluate the performance of multimodal transportation integration facilities at Serang Station, a major transportation hub in the Jakarta-Merak corridor serving 15,000 passengers per day. Key issues identified include fragmented pedestrian paths, a 450 m intermodal distance exceeding the 300 m TOD standard (SNI 03-7065-2005), limited covered waiting areas, and a lack of directional signs. This evaluation addresses the urgent need to improve travel efficiency and user satisfaction, contributing to sustainable urban development and reducing economic losses due to congestion. The Customer Satisfaction Index (CSI) was used to measure user perceptions of 16 facility attributes, and Importance-Performance Analysis (IPA) was used to prioritize improvements based on the gap between expectations and performance. The results showed very low levels of satisfaction with disabled access (CSI = 20%), lighting, zebra crossings, and bus stops (CSI = 20–46%), far below the average CSI of 52.52%, making them top priorities for improvement. Meanwhile, cleanliness, public restrooms, and gentle slopes meet user expectations. Recommendations include improved lighting, a microtransit hub within a 500-meter radius, additional trash bins, improved access for the disabled, improved markings/signage, and the construction of protected bus stops to support equitable, efficient, and sustainable urban mobility.